An Integrated Picture Fuzzy Set with TOPSIS-AHP Approach to Group Decision-Making in Policymaking under Uncertainty - Long Cu Kim (International Journal of Mathematical, Engineering and Management Sciences, 2021)
Group Decision-Making techniques have been applied to combine a group of decision maker’s preferences to deal with an evaluation of alternatives in a static environment. However, these conventional techniques are only concerned with an evaluation in a static environment. They cannot solve the policy evaluation problems in a dynamic environment or under uncertainty. This paper has presented a novel proposed model to handle the policy evaluation problems under uncertainty by integrating the Picture fuzzy set with the traditional TOPSIS-AHP model. The qualitative and quantitative factors are been quantified by using Picture fuzzy set to evaluate alternatives in order to make complex decisions in a dynamic environment. To validate the proposed model, a numerical example was illustrated meticulously. The experimental results also proved that the proposed method based on the indicator groups in the final urban development project in Vietnam combined with the expert's expertise and the decision-maker's preference gives the more confident evaluation result compared to the state-of-the-art works by applying the fuzzy decision point of the policy.